2020
DOI: 10.7554/elife.54183
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporally precise optogenetic activation of sensory neurons in freely walking Drosophila

Abstract: Previous work has characterized how walking Drosophila coordinate the movements of individual limbs (DeAngelis et al., 2019). To understand the circuit basis of this coordination, one must characterize how sensory feedback from each limb affects walking behavior. However, it has remained difficult to manipulate neural activity in individual limbs of freely moving animals. Here, we demonstrate a simple method for optogenetic stimulation with body side-, body segment-, and limb-specificity that does not require … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 70 publications
(102 reference statements)
1
6
0
Order By: Relevance
“…These results reproduce the known effects of natural sugar or bitter (Flood et al, 2013;Thoma et al, 2016;Marella et al, 2006;Joseph and Heberlein, 2012;Das et al, 2014;Schwaerzel et al, 2003), providing reassurance that our activation paradigms are relevant to natural behavior. Our results also align with other studies that reported effects on locomotion or innate preference using optogenetic taste neuron activation (Aso et al, 2014;Tadres and Louis, 2020;Mohammad et al, 2017;Haberkern et al, 2019;DeAngelis et al, 2020;Stern and Yang, 2017).…”
Section: Behavioral Effects Of Optogenetic Taste Activationsupporting
confidence: 92%
“…These results reproduce the known effects of natural sugar or bitter (Flood et al, 2013;Thoma et al, 2016;Marella et al, 2006;Joseph and Heberlein, 2012;Das et al, 2014;Schwaerzel et al, 2003), providing reassurance that our activation paradigms are relevant to natural behavior. Our results also align with other studies that reported effects on locomotion or innate preference using optogenetic taste neuron activation (Aso et al, 2014;Tadres and Louis, 2020;Mohammad et al, 2017;Haberkern et al, 2019;DeAngelis et al, 2020;Stern and Yang, 2017).…”
Section: Behavioral Effects Of Optogenetic Taste Activationsupporting
confidence: 92%
“…Because the entire body of every animal is illuminated, this approach relies entirely on genetics for targeting. Recent work has used stochastic spatially varying illumination patterns in open loop from a projector [49] or cellphone [50] to probe the spatial dependence of optogenetic stimulation. But because these methods are open loop, they cannot target stimulation specifically to any animal or body part.…”
Section: Introductionmentioning
confidence: 99%
“…1 (Demir et al, 2020). The second is a method for patterned optogenetic stimulation using a light projector mounted above the arena (DeAngelis et al, 2020) (Fig. 2a).…”
Section: Resultsmentioning
confidence: 99%
“…Experiments were recorded with a FLIR Grasshopper USB 3.0 camera with IR-pass filter at 60 Hz. Optogenetic stimuli were delivered using a LightCrafter 4500 digital light projector mounted 310 mm above the arena, illuminating an area larger than in the original method (DeAngelis et al, 2020). Only the red LED (central wavelength 627 nm) was used throughout this study.…”
Section: Behavioral Assay and Optogenetic Stimulationmentioning
confidence: 99%